2013
DOI: 10.1016/j.jsbmb.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Changing glucocorticoid action: 11β-Hydroxysteroid dehydrogenase type 1 in acute and chronic inflammation

Abstract: Highlights► 11β-HSD1 converts inert glucocorticoids into active forms, amplifying glucocorticoid action. ► 11β-HSD1 is markedly induced by pro-inflammatory cytokines. ► 11β-HSD1 deficiency/inhibition worsens acute inflammation. ► 11β-HSD1 inhibition reduces inflammation in obesity or atherosclerosis. ► An increased angiogenic response may underlie some of the benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
96
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 139 publications
2
96
0
Order By: Relevance
“…However, 11bHSD1 and 11bHSD2 expression in macrophages, and their contribution to the development of foam cells and progression of atherosclerosis, remain unclear. The expression of 11bHSD1 in macrophages is dependent on their activation state [46]. Thus, M1 polarization of native macrophages by lipopolysaccharides induces 11bHSD1 expression; in contrast, polarization to M2 by IL4/IL13 has little effect on 11bHSD1 expression.…”
Section: Discussionmentioning
confidence: 97%
“…However, 11bHSD1 and 11bHSD2 expression in macrophages, and their contribution to the development of foam cells and progression of atherosclerosis, remain unclear. The expression of 11bHSD1 in macrophages is dependent on their activation state [46]. Thus, M1 polarization of native macrophages by lipopolysaccharides induces 11bHSD1 expression; in contrast, polarization to M2 by IL4/IL13 has little effect on 11bHSD1 expression.…”
Section: Discussionmentioning
confidence: 97%
“…In placental mammals, cortisol/corticosterone levels in the maternal circulation are 5-to 10-fold higher than in the fetus (Dalle et al, 1978;Montano et al, 1991), a gradient thought to be maintained by high placental 11␤-HSD-2 (Brown et al, 1996). This enzyme catalyses the inactivation of maternal glucocorticoids before they are transferred to the fetus (Chapman et al, 2013;Cottrell et al, 2013). Down-regulation of placental 11␤-HSD-2, in addition to being correlated with a significant reduction in fetal weight both in humans and rodents (Lindsay et al, 1996), increases fetus vulnerability to the detrimental effects of maternal HFD.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to speculate that the reduced expression of the 11ˇ-HSD-1 gene at that time could be associated to a HFD-induced impaired fetal development, further supported by the reduced fetal weight registered at the same time (G18). Thus, it is reasonable to state that maternal HFD mediates an imbalance in the expression of the genes that regulate the time window of fetal exposure to maternal glucocorticoids (Chapman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the identification of 11β-HSD1 more than half a century ago, there has been little investigation into its physiological role until relatively recently (13). It is notable that the severity of acute inflammation is greater in 11β-HSD1-deficiency or inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the severity of acute inflammation is greater in 11β-HSD1-deficiency or inhibition. However, in certain conditions in which inflammation is invovled, such as obesity or diabetes, 11β-HSD1-deficiency or inhibition appears to be beneficial and has been shown to reduce inflammation (13). Data have shown that IL-1β induces the expression of 11β-HSD1 mRNA (14).…”
Section: Discussionmentioning
confidence: 99%